PENGARUH PERBEDAAN JENIS UMPAN TERHADAP HASIL TANGKAPAN IKAN SIDAT (ANGUILLA SPP) DI KABUPATEN LOMBOK TIMUR - Sulastri; Handri Jurya Parmi (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2024)
Catching eels (Anguilla spp) in East Lombok using gear traditional minimalist, like fishing usual (line fishing), traps (traps), fishing (fishing rod) and others by using different types of bait such as shrimp, worms, crabs, gastropods, frogs and others. Results arrests were made other than that is not optimal due East Lombok people know less effective type of bait in fishing effort eel (Anguilla spp). The method used in this research is an experimental method is a method by doing experiments to see something that results and further results that would confirm how the causal relationship between the variables investigated. The data collection involves collecting primary data. Primary data obtained from the research process directly by way of the usual operate a fishing pole (fishing line) ditiga Watershed (DAS) that streams Lengkok (Labuhan Haji), river flow Lenek Bere (Korleko), and streams Koko` Keru (Tirpas ) East Lombok. Analysis of the data used to determine the effect of different types of bait to catch eel is a model of randomized block design (RAK) and data analysis used to determine the type of feedback the most influential is the advanced test Significant Difference (BNT). The results of this research indicate that the value of F count larger than F table at 5% and 1% of the variance group (5.34> 2.59 and 3.89) and the variance of treatment (10.43> 3.63 and 6.22), meaning that the effect of different types of bait eels (Monopterus albus), earthworm (Lumbricus rubelus) and frogs (Fejervarya cancrivora) very significant effect on the fish catch eel. BNT analysis results showed that the treatment type of bait to use bait earthworm (Lumbricus rubelus) real effect it can be seen by looking at the value of BNT worms bigger than BNT0.05 (0.89> 0.76), whereas treatment with frog baits (Fejervarya cancrivora) very significant effect this is because the value is greater than BNT frog BNT0.05 and BNT0.01 (2.44, 1.56 and 1:22> 0.76 and 1.05).